Staged surgical management of an extensive penoscrotal and perineal microcystic lymphatic malformation in an adolescent male - Aakanksha Desai; Aoife Rice; Phil Urquhart; Roy Kimble (Elsevier, 2020)
This case reports details a successful approach to the surgical management of an extensive penoscrotal microcystic lymphatic malformation in an adolescent male. The patient had staged total excision of skin and subcutaneous tissue and reconstruction was achieved with a combination of thick and thin split thickness grafts.